Direct Method in Islamic Religious Education: Conceptual Framework and Implementation in Indonesia - Asrori Asrori; Aldo Redho Syam (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2024)
The Direct Method, characterized by a focus on oral communication and direct practice, has been widely discussed in the context of language learning. Its application in Islamic religious education, however, remains less explored. This study aims to fill this gap by examining the theoretical underpinnings of the Direct Method and its implementation in Islamic religious education in Indonesia. The primary objective of this research is to comprehensively explore the concept of the Direct Method and its application in the teaching of Islamic religious studies. This includes understanding the theoretical foundations of the method and assessing its practical application in various educational settings, such as schools and madrasahs in Indonesia. This study employs a qualitative research approach, specifically library research. Data were collected through an extensive review of literature from primary and secondary sources, including books, journal articles, and other relevant publications. Data analysis was conducted using document analysis and thematic analysis techniques. The findings reveal that the Direct Method is highly effective in enhancing students' understanding and skills in Islamic religious education. The method's emphasis on direct interaction and immediate feedback from teachers fosters a conducive and personalized learning environment. However, challenges such as limited time and resources were identified as potential barriers to its effective implementation. To maximize the benefits of the Direct Method, ongoing support and training for teachers are essential. Additionally, adequate resources and institutional support are necessary to overcome the identified challenges. Future research should continue to explore innovative strategies to enhance the effectiveness of the Direct Method in various educational contexts.